2016
DOI: 10.1007/s10544-016-0079-6
|View full text |Cite
|
Sign up to set email alerts
|

Lab on a chip-based hepatic sinusoidal system simulator for optimal primary hepatocyte culture

Abstract: Primary hepatocyte cultures have been used in studies on liver disease, physiology, and pharmacology. While they are an important tool for in vitro liver studies, maintaining liver-specific characteristics of hepatocytes in vitro is difficult, as these cells rapidly lose their unique characteristics and functions. Portal flow is an important condition to preserve primary hepatocyte functions and liver regeneration in vivo. We have developed a microfluidic chip that does not require bulky peripheral devices or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…Indeed, continuous perfusion culture improves oxygen and nutrition supply for cells, as previously predicted computationally [63][64][65][66][67]. It has also been reported that gene expression profiles collected from hepatocyte cells cultured on a microfluidic chip with dynamic flow conditions showed more hepatocyte-specific characteristics than cells in static conditions [68].…”
Section: Accepted Manuscriptmentioning
confidence: 58%
See 1 more Smart Citation
“…Indeed, continuous perfusion culture improves oxygen and nutrition supply for cells, as previously predicted computationally [63][64][65][66][67]. It has also been reported that gene expression profiles collected from hepatocyte cells cultured on a microfluidic chip with dynamic flow conditions showed more hepatocyte-specific characteristics than cells in static conditions [68].…”
Section: Accepted Manuscriptmentioning
confidence: 58%
“…In general, a microwell-based µSFC needs a specified number of microwells and a microchannel network to deliver the culture medium ( Figure 5A-E). For spheroid generation, the cell suspension is introduced at the inlet, usually with a cell density of 105 to 107 cells/ml [6,68,96], depending on the cell type ( Figure 5A). To achieve uniform cell seeding in microwells and uniformly sized spheroids, the cell suspension should fill the device entirely before cells begin to deposit in the microwells.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Few minutes are needed that cells deposit on the bottom of the microwells and the microchannel ( Figure 4B). The cells that did not trap in the microwells are pushed out of the chip before the cells make aggregations and clog microchannels [8,24,103] (Figure 4C). Next, the cells begin aggregation and form spheroids ( Figure 4D) and are culture for drug screening ( Figure 4E).…”
Section: Microfluidic Methods For Spheroid Culturementioning
confidence: 99%
“…Although human embryonic stem cells have been successfully used for differentiation into cholangiocytes with formation of polarized cysts and biliary ducts in 3D cell culture (Dianat et al, 2014), recapitulation of the polarized architecture of hepatic cords with human cells using the sandwich method is awaited. Ultimately, these relatively simple monoculture and coculture systems can serve as basis to include more complex parameters of liver physiology, such as a directional movement of medium to mimic sinusoidal blood flow and shear forces (Burkhardt et al, 2014; Choi et al, 2016). …”
Section: Mimicry Of Tissue Architecture In 3d Cell Culture For Toxmentioning
confidence: 99%